Map of Indonesia's Human Resources Needs In Supporting the Transformation of the Downstream Industry - Andri Hermawan; Lilis Suharti; Muangsal Muangsal (Jurnal Ekuisci, 2026)
Background. Indonesia's downstream industrialization (downstreaming) program—transforming from a raw material exporter to a producer of high-value-added products—represents one of the most significant structural changes in Indonesia's modern economic history. The success of this transformation fundamentally depends on having human resources (HR) with the right competencies, in adequate quantities, and at the right times. However, Indonesia currently faces a substantial HR gap between the exponentially growing needs of the downstream industry and existing industrial HR production capacity. Aims. This study aims to quantitatively and systematically analyze Indonesia's HR needs to support the industrial downstream program over 2025–2045. Using an Occupational Demand Modeling (ODM) methodology combined with Global Value Chain (GVC) analysis and Labor Market Intelligence, this research identifies 12 critical competency areas most needed in Indonesia's downstream industrial ecosystem, quantitatively projects HR requirements per field, identifies gaps between current educational supply capacity and projected industry demand, and formulates structured HR development policy recommendations. Result. Key findings indicate that Indonesia requires at least an additional 4.8 million skilled workers in critical downstream fields during 2025–2035, with the largest deficits in metallurgy and materials engineering (680,000 deficit), chemical process engineering (540,000), electrical engineering and industrial automation (720,000), and supply chain management (390,000). In 2036–2045, cumulative needs increase to 12.6 million additional HR as downstream expansion enters new sectors. Conclusion. The study emphasizes that without systemic acceleration in industrial HR production—through higher education and vocational curriculum reform, massive reskilling programs, and industry-university partnerships—Indonesia's downstream transformation potential cannot be optimally realized.